2020
DOI: 10.1186/s12967-020-02594-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Is there a role for immunonutrition in obese patient?

Abstract: On December 12, 2019 a new coronavirus (SARS-CoV-2) emerged in Wuhan, China, triggering a pandemic of severe acute respiratory syndrome in humans (COVID-19). Today, the scientific community is investing all the resources available to find any therapy and prevention strategies to defeat COVID-19. In this context, immunonutrition can play a pivotal role in improving immune responses against viral infections. Immunonutrition has been based on the concept that malnutrition impairs immune function. Therefore, immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 168 publications
(239 reference statements)
3
69
0
1
Order By: Relevance
“…[272][273][274] Moreover, research studies reported that the immune physiology could be restored to the normal level by consuming a balanced diet and, if necessary, supplementing micronutrients and trace elements. 274,275 In this manner increases resistance to infection and supports quicker recovery from infectious diseases by reducing both inflammation and oxidative stress triggered by several reasons. 255,272,274,275 By this means, micronutrient insufficiencies have been identified as an international public health concern.…”
Section: Role Of Micronutrients Vitamins and Other Trace Elements Imentioning
confidence: 99%
See 1 more Smart Citation
“…[272][273][274] Moreover, research studies reported that the immune physiology could be restored to the normal level by consuming a balanced diet and, if necessary, supplementing micronutrients and trace elements. 274,275 In this manner increases resistance to infection and supports quicker recovery from infectious diseases by reducing both inflammation and oxidative stress triggered by several reasons. 255,272,274,275 By this means, micronutrient insufficiencies have been identified as an international public health concern.…”
Section: Role Of Micronutrients Vitamins and Other Trace Elements Imentioning
confidence: 99%
“…274,275 In this manner increases resistance to infection and supports quicker recovery from infectious diseases by reducing both inflammation and oxidative stress triggered by several reasons. 255,272,274,275 By this means, micronutrient insufficiencies have been identified as an international public health concern. 258,276,277 A recent study by Darnton-Hill reported that selenium, iron, potassium, sodium, calcium, magnesium, folic acid, copper, and zinc play an important role in improving the immune physiology and patient recovers earlier and decrease hospital stay among COVID-19 patients.…”
Section: Role Of Micronutrients Vitamins and Other Trace Elements Imentioning
confidence: 99%
“…It is possible that stay-at-home policies in conjunction with social distancing may exacerbate weight gain via their effects on physical activity and diet patterns. Current data and expert opinion highlight the significance of vitamins D and C, minerals such as zinc, nutraceuticals such as curcumin, and the maintenance of adequate hydration, proposing also moderate consumption of fat, preferably unsaturated fats, and avoidance of salt and sugar intake [ 94 , 185 , 186 ]. The Mediterranean diet represents one of the healthiest dietary approaches globally, recognized for its demonstrated preventive actions in T2DM and cardiometabolic disorders in a plethora of trials [ 187 ].…”
Section: Implications In Prevention and Treatmentmentioning
confidence: 99%
“…It is possible that stay-at-home policies in conjunction with social distancing may exacerbate weight gain via their effects on physical activity and diet patterns. Current data and expert opinion highlight the significance of vitamins D and C, minerals such as zinc, nutraceuticals such as curcumin, and ✓ HbA1c should be assessed in patients with COVID-19 with hyperglycemia and/or ketoacidosis to identify potential undiagnosed DM ‡ Position statement by the European Society of Cardiology, the American College of Cardiology, the American Heart Association, and the Heart Failure Society of America ACE, angiotensin-converting enzyme; AKI, acute kidney injury; ALT, alanine aminotransferase; ARBs, angiotensin receptor blocker; CDC, Centers for Disease Control and Prevention; CRP, C-reactive protein; CV, cardiovascular; DIC, disseminated intravascular coagulation; DKA, diabetic ketoacidosis; DM, diabetes mellitus; DPP-4, dipeptidyl peptidase 4; eGFR, estimated glomerular filtration rate; ESR, erythrocyte sedimentation rate; GLP-1R, glucagon-like peptide 1 receptor; IL, interleukin; MERS, Middle East respiratory syndrome; PPAR-γ, peroxisome proliferator-activated receptors-γ; SGLT2: sodium glucose co-transporter 2; TCZ, tocilizumab the maintenance of adequate hydration, proposing also moderate consumption of fat, preferably unsaturated fats, and avoidance of salt and sugar intake [94,185,186]. The Mediterranean diet represents one of the healthiest dietary approaches globally, recognized for its demonstrated preventive actions in T2DM and cardiometabolic disorders in a plethora of trials [187].…”
Section: Implications In Prevention and Treatmentmentioning
confidence: 99%
“…Starting with and maintaining an adequate LM is compulsory to reach all the benefits of the fasting state in terms of body composition. Maintaining a correct nutrition status is crucial, especially in a period when the immune system is stimulated and involved in internal reset [ 128 , 129 ]. Water intake is also important.…”
Section: Guidelinesmentioning
confidence: 99%